Multidimensional Welfare Comparisons of EU Member States Before, During, and After the Financial Crisis: A Dominance Approach - M. Azhar Hussain; Nikolaj Siersbæk; Østerdal Lars Peter (Copenhagen Business School (CBS), Department of Economics, 2018)
How did the financial crisis affect population welfare in EU member states in key dimensions such as income, health, and education? We seek to answer this question by way of welfare comparisons between countries and within countries over time,using EU-SILC data. Our study is novel in using a multidimensional first order dominance comparison approach on the basis of multi-level ordinal data. We find that the countries most often dominated are southern and eastern European member states, and the dominant countries are mostly northern and western European member states. However, for most country comparisons, there is no dominance relationship. Moreover, only a few member states have experienced a temporal dominance improvement in welfare, while no member states have experienced a temporal dominance deterioration during the financial crisis.
hdl:10398/9657
Keywords: I31; I32; O52; 330; first order dominance; multidimensional well-beeing; multi-level indicators; EU-SILC